State and capital in Mexico : development policy since 1940 - Cypher, James M. (Series in political economy and economic development in Latin America., 2019)
In development studies it is widely recognized that state intervention has been more profound in Mexico than elsewhere in Latin America. Since the 1930s, successive governments have actively adopted import substitution as a means of spurring economic growth, often with spectacular results. The collapse of the petro-boom in 1982, however, brought an